Update in the management of severe traumatic brain injury - Alvarez, Eva Esther Tejerina; Vivar, Fernando Frutos; Puch, Irene Cortés; de la Torre, Andrés Esteban; Balanza, José Ángel Lorente (Clinical and Biomedical Research, 2014)
Traumatic brain injury is the main cause of death and disability in the young population, which presumes a large number of years of potential life lost and a great economic impact. Vital and functional outcomes after suffering a traumatic brain injury depend both on the severity of the initial biomechanical impact (primary injury) and on the presence and the severity of systemic or intracranial insults that magnify and/or produce new brain injuries, the so-called secondary injuries. Currently, no treatment in effective in improving functional recovery, except for usual medical care. Therefore, the main purpose of the care provided to a patient with severe cranial trauma is based on preventing and treating secondary brain injuries by maintaining an adequate cerebral perfusion and oxygenation. Increased intracranial pressure is associated with mortality and with unfavorable functional outcomes is patients with severe traumatic brain injury. The main clinical practice guidelines recommend using a number of staggered therapeutic measures. However, although these measures seem to be efficient in reducing intracranial pressure, this effect is not often translated into clinical improvement. This review describes the essential principles of the management of patients with severe traumatic brain injury in intensive care units.